Role of Contrastive and Noncontrastive Associates in the Interpretation of Focus Particles. Issue 8 (17th November 2017) - Gotzner, Nicole; Spalek, Katharina
Abstract : The present research examines the mechanisms underlying the comprehension of focus alternatives. In particular, we investigate whether listeners determine alternatives based on general semantic priming mechanisms or whether they only consider contrastive alternatives, elements that can replace the expression in focus. In a probe recognition experiment, we compare the retrieval of contrastive alternatives with that of general associates of a focused expression across conditions with focus particles ( only or also ) and a condition without a particle. The rationale is that focus particles like only necessarily involve the computation of alternatives and should therefore affect the retrieval of relevant alternatives. The results of the study show that focus particles influence the retrieval of unmentioned contrastive alternatives but not that of general associates. Therefore, we suggest that alternatives are determined by a specialized mechanism that takes into account whether or not an element can replace a focused expression and only these possible replacements are relevant for the processing of focus particles.